Evaluating Repeatability of RTK (GPS and Galileo/GPS) performance in the analysis of points located in areas with and without obstructions - Pirti, Atinc; Yucel, M. Ali (SCIENDO, 2022)
Galileo is Europe's Global Navigation Satellite System (GNSS), which provides improved positioning and timing data with significant benefits for many European services and users. Galileo enables users to know their exact location with greater precision than other available systems. Access to the Galileo signal in the obstructed and unobstructed environment provides benefits and opportunities for work, thanks to the improved performance and accuracy. The use of a Galileo-enabled receiver increases the number of satellites in view significantly. When compared to the performance of single-constellation receivers, this significantly reduces the time required to obtain a position with centimetre-level accuracy. The results indicate the current Galileo constellation's suitability for high-precision RTK applications, as well as improved availability, accuracy, reliability, and time-to-fix in the obstructed and unobstructed environments. The results of RTK GPS and RTK GPS/Galileo obtained at different times of the same day by using two reference points were compared. The results of this study illustrate that integrating RTK GPS system with Galileo is favorable for surveying applications (cm accuracy). This study shows that in surveying applications requiring centimetre accuracy, the RTK GP S/Galileo method can replace other survey methods (Total Station).
Keywords: RTK GPS/Galileo; RTK GPS; Woodland; Accuracy; Total station; FOREST CANOPY; GLONASS; BEIDOU; QUALITY; IGS; Remote Sensing